An exploration of the relationship between eWOM on Chinese social media, customer trust, and value co-creation - Shen, Yaqiong (2017)
This dissertation attempts to investigate the relationship between eWOM on Chinese social media, customer trust, and value co-creation. Data was collected through a series of interviews with sixteen individuals who are frequent users of Chinese social media and have value co-creation experiences. The research was conducted by semi-structured interviews following an interview guide covers the main topic and interviewees own experience. In this study, a thematic analysis was adopted to analyse the interview data.